INTEGRASI PASAR MODAL ISLAM: STUDI DI LIMA NEGARA ASEAN DAN DJIA - Muhammad Al Faridho Awwal; Ita Eviyanah; Abdul Qoyum (Universitas Muhammadiyah Prof Dr Hamka, 2022)
This study aims to determine the short- and long-term relationship between the Islamic capital market in Southeast Asia and the DJIA. This study takes data from the Islamic capital markets of ASEAN-5 countries, namely the Jakarta Islamic Index (JII), FTSE Malaysia, FTSE SET Sharia Thailand, FTSE SGX Sharia Singapore and MSCI Philippines and DJIA. A total of 211 weekly observations of each index were observed from 04 January 2015, to 03 February 2019. Author have found that the Islamic capital market is integrated in all ASEAN-5 countries including the DJIA. This study also finds that the Malaysian Islamic capital market and DJIA have the most influence on the ASEAN-5 Islamic capital market, as shown by the VDC test. Keywords; ASEAN, DJIA, Capital Market